Geologi Dan Analisis Kuat Tekan Andesit Daerah Wates Dan Sekitarnya, Kecamatan Wonotunggal, Kabupaten Batang, Provinsi Jawa Tengah - Naldi Ode Jimu,; Herning Dyah K.W,; Winarti, (ReTII, 2023)
Administratively, the research area is located in Central Java Province, Batang Regency, Wonotunggal District, Village, Wates and its surroundings. Astronomically the study area is located at coordinates 109°46' 33.4'' E - 109 43' 18.7 E and 7° 02' 06.1" S - 6 57' 12.9" S with an area of study ± 54 km2. The research method used is the geological surface mapping method. This method is carried out by direct observation of geological data exposed on the surface of the earth, including rock types, rock layers, rock slopes, contact boundaries, geological structures and other geological phenomena. Based on detailed mapping results and based on morphometric and morphogenetic calculations: Denudational hill and slope geomorphological unit (D1). Slope foot geomorphological unit (D7). with one drainage pattern, namely dendritic and adult areas. The stratigraphic relationship of the study area is composed of four units sorted from old to young, namely Damar Formation sandstone units (Plistocene), andesitic breccia units of Jembangan Volcano (Plistocene), andesite lava units of Jembangan Volcano (Plistocene), lava deposit units (Holocene). The natural resources in the study area consist of land resources, water resources and mineral resources C. The natural disasters in the study area are landslides and floods. Based on the results of laboratory analysis of andesite rock samples, it can be concluded that in general the location of the research area can be used as a building material with an average compressive strength value of lp 60 (2223.385 kg/cm2), and lp 38 (599.859 kg/cm2). On the andesite frame lp 60 and andesite lava on alp 38 meet the requirements for building materials for house foundations, road paving, bridges, and airport runway foundations.